Campus Learning Based on AI: Implementation of ChatGPT in AILS and Its Implications for Curriculum Development in Indonesia - Trilaksana, Herry; Soelistiono, Soegianto; Wahidin (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2024)
The application of Artificial Intelligence (AI) in the context of higher education has increasingly drawn attention, especially with rapid technological advancements. One intriguing implementation of AI is ChatGPT, a generative language model capable of interacting naturally with users. In this study, we explore how ChatGPT can be utilized in campus learning in Indonesia using the Artificial Intelligent Learning System (AILS) and how its usage impacts curriculum development. Through literature analysis and case studies, we investigate various ways in which ChatGPT has been applied in the campus learning environment, including student-teacher interactions, learning assistance, and curriculum content development through AILS. We also consider the positive and negative impacts of using ChatGPT in the learning process, including increased efficiency, student engagement, and challenges that may arise in integrating this technology with existing curricula. The findings of this study provide valuable insights for education decision-makers, educators, and curriculum developers regarding the potential use of ChatGPT in the context of campus learning in Indonesia through AILS. We also highlight the need for collaboration between technology and educators in designing the right strategies to optimize the benefits of AI in enhancing the quality of higher education.